DUALITAS PRAKTIK PERKAWINAN MINANGKABAU - Zainal Arifin (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
This paper aims to understand duality of Minangkabau marriage. The results of the research indicates that the decision making process which proceed a marriage are not fully determined by the adaik’s norms, but also being influenced by “politics of marriage” of the actor and kinship members who are to be interwoven in the proposed extended family. The decision making process proceeding marriages in Minangkabau is essentially a synthesis of adaik, which permits certain cultural liberties to actor and family members who will then be part of the extended family.